Audiobook, audio podcast, audio series – modern formats of the media space - V. Yu. Bal (Библиосфера, 2020)
The article discusses modern audioformats – audiobook, audio series and audio podcast. Now these formats have gained great popularity and demand, considerable market weight with their own segment, the growth of which experts note. The research material is audio products of the modern market, which reflect the trends in the development of audio literature in the current media environment. The scientific novelty of the work consists in the consideration of an audiobook, an audio series and an audio podcast in the context of a new stage in the development of audio culture. The problem of popularity of the studied audio products is considered in direct dependence on audio reading. It is understood as a modern modification of auditory reading, as a reader’s practice due to the qualitative changes in the material and technical base for creating audio records, for their copying and use. The analysis of audio formats in the informational, sociocultural and cognitive aspect of the modern media consumption allows the determination new editorial approaches to the work with audio texts. Conclusions are as follows: one can observe the tendency to transit from voicing printed texts to creating texts specially for voicing; there is a reduction in the novel form, stories become popular; the editing of audio books and audio series requires support from sound design principles; the editorial and director’s task on preparing podcasts is associated with the compositional alignment of several voices of storytellers, forming a single ideological and thematic field.